2013
DOI: 10.1177/0956462413496771
|View full text |Cite
|
Sign up to set email alerts
|

Polyactin A increases CD4+ T-cell counts in HIV-infected individuals with insufficient immunologic response to highly active antiretroviral therapy

Abstract: We conducted a study to determine whether an immunomodulator, polyactin A, is able to enhance the immunologic response in patients with insufficient immunologic response to highly active antiretroviral therapy. From 783 patients, 48 were eligible and were randomly assigned to an experimental group receiving polyactin A for 3 months or a control group. CD4(+) T-cell counts in the experimental group increased from 201 ± 31 to 228 ± 38 cells/µl after treatment (p < 0.001). CD4(+) T-cell counts in the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…MT has been developed and used as an immunomodulator and adjuvant treatment for immunocompromised diseases, such as cancer and chronic hepatitis B, in China for over 30 years. 7 MT modulates the immune function by a variety of pathways. Previous studies have suggested the effect of MT on CD4 + T-cell count and CD4 + /CD8 + ratio.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 2 more Smart Citations
“…MT has been developed and used as an immunomodulator and adjuvant treatment for immunocompromised diseases, such as cancer and chronic hepatitis B, in China for over 30 years. 7 MT modulates the immune function by a variety of pathways. Previous studies have suggested the effect of MT on CD4 + T-cell count and CD4 + /CD8 + ratio.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Mannatide (MT), also known as a‐Polyactin or Polyactin A (PAA), is a heteropolysaccharide isolated from fermentation broth of buccalalpha‐haemolytic streptococcus strain No.33. MT has been developed and used as an immunomodulator and adjuvant treatment for immunocompromised diseases, such as cancer and chronic hepatitis B, in China for over 30 years 7 . MT modulates the immune function by a variety of pathways.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…33.1. PA is an immunomodulator and adjuvant that has been used for the treatment of impaired immunity, including cancer and chronic hepatitis B, in China for more than 30 years [16, 17]. A previous study showed that PA improved the production of the antibodies against hepatitis B surface antigen (anti-HBs) after hepatitis B virus vaccine immunization [18].…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, with great interest we read the article by Su et al. titled “Polyactin A increases CD4 + T cell counts in HIV-infected individuals with insufficient immunologic response to highly active antiretroviral therapy”, 2 which was a prospective, randomized, open-label, parallel clinical trial study. This is commendable, however there were few studies on the essential problem with Polyactin A (PAA).…”
mentioning
confidence: 99%